Intensification of Livestock Production Systems in the North West Region of Cameroon : A South-to-South Collaboration for Technology Transfer, The Tugi Silvopastoral Project - World Bank (Washington, DC, 2013)
The Tugi Silvo-pastoral Project (TUSIP) is a South-South Cooperation between the Tropical Agriculture Research and Higher Education Centre (CATIE) based in Costa Rica (www.catie.ac.cr) and the Akwi Memorial Foundation (AMF) based in the North West Region of Cameroon. The main goal of TUSIP was to assess the environmental benefits of a set of silvo-pastoral practices and to empower traditional livestock farmers in Tugi Village by enhancing their capability to manage available crop-animal systems and natural resources in a sustainable manner. TUSIP made efforts in the rehabilitation of degraded pasturelands to ensure adequate year-round availability of forages to increase animal productivity in a sustainable manner, consequently contributing to improving the livelihoods of rural families who depend on livestock activities in Tugi. The project put emphasis on (1) modifying the traditional crop-livestock systems through the implementation of silvo-pastoral options, which helped to diversify income sources, and (2) improving soil fertility, while (3) restoring ecosystem services that were affected by the change in land use from forests to degraded pastures. The project applied participatory methodologies to build the capability of the Tugi population to replicate the technological innovations introduced by TUSIP.